Platelet-Rich Fibrin in Third Molar Surgery: Systematic Review and Meta-Analysis Protocol. Issue 2 (June 2022) - Salas, Gaston A.; Lai, Shuheng A.; Verdugo-Paiva, Francisca; Requena, Roberto A.
Objective: The objective of this systematic review is to assess the effectiveness and safety of platelet-rich fibrin (PRF) in third molar surgery. Data Sources: A comprehensive search strategy is meant to be used in an attempt to identify all relevant randomized controlled trials (RCTs), ongoing investigation reported in specialty congresses and trials regardless of language or publication status (published, unpublished, in press and in progress). Searches will be conducted in the Cochrane Central Register of Controlled Trials (CENTRAL), PUBMED, Embase, Lilacs, the International Clinical Trials Registry Platform (ICTRP), ClinicalTrials.gov, US National Institutes of Health (NIH), grey literature and in specialized congresses and conferences. Eligibility Criteria: We will include randomized trials evaluating the effect of PRF on wound healing after third molar surgery. Two reviewers will independently screen each study for eligibility, data extraction and risk of bias assessment using Cochrane "risk of bias" tool. We will pool the results using meta-analysis and will apply the GRADE system to assess the certainty of the evidence for each outcome. Ethics and Dissemination: As researchers will not access information that could lead to the identification of an individual participant, obtaining ethical approval was waived.